2012
DOI: 10.1103/physrevb.85.075404
|View full text |Cite
|
Sign up to set email alerts
|

Higher-order contributions to the Rashba-Bychkov effect with application to the Bi/Ag(111) surface alloy

Abstract: In order to explain the anisotropic Rashba-Bychkov effect observed in several metallic surfacestate systems, we use k·p perturbation theory with a simple group-theoretical analysis and construct effective Rashba Hamiltonians for different point groups up to third order in the wavenumber. We perform relativistic ab initio calculations for the (• Bi/Ag(111) surface alloy and from the calculated splitting of the band dispersion we find evidence of the predicted third-order terms. Furthermore, we derive expression… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
110
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(120 citation statements)
references
References 48 publications
9
110
0
1
Order By: Relevance
“…The apparently larger splitting δk y ≈ 0.1Å −1 of the peaks a, b and e, f compared to the K and M directions is due to the intersection under a finite angle (≈60 • ) with respect to the high-symmetry directions. Moreover, the S z components at these k points are nonzero in consistency with the Rashba model including third-order terms within C 3v symmetry [43,44]. In other words, the existence of finite S z components corroborates that higher-order Rashba terms are necessary for the description of the band structure.…”
Section: Spin-resolved Arpes Measurementssupporting
confidence: 59%
“…The apparently larger splitting δk y ≈ 0.1Å −1 of the peaks a, b and e, f compared to the K and M directions is due to the intersection under a finite angle (≈60 • ) with respect to the high-symmetry directions. Moreover, the S z components at these k points are nonzero in consistency with the Rashba model including third-order terms within C 3v symmetry [43,44]. In other words, the existence of finite S z components corroborates that higher-order Rashba terms are necessary for the description of the band structure.…”
Section: Spin-resolved Arpes Measurementssupporting
confidence: 59%
“…Indeed, even the dispersion of the topologically protected surface states on these materials can be viewed in the context of anisotropic Rashba-type splitting [17,18]. For several systems, it has been found that the simple Rashba effect which is linear in k is insufficient to describe the spin-orbit splitting and further correction terms such as a cubic anisotropy [17,18] and a cubic isotropic correction were introduced [19].…”
mentioning
confidence: 99%
“…Indeed, even the dispersion of the topologically protected surface states on these materials can be viewed in the context of anisotropic Rashba-type splitting [17,18]. For several systems, it has been found that the simple Rashba effect which is linear in k is insufficient to describe the spin-orbit splitting and further correction terms such as a cubic anisotropy [17,18] and a cubic isotropic correction were introduced [19].Here we show that strongly Rashba-split 2DEGs with intriguing new properties can be created by surfacedoping of the topological insulator Bi 2 Te 2 Se. The band splitting in these 2DEGs is anisotropic to a degree that the bands are strongly spin-split in one direction and almost degenerate in another, possibly paving the way towards new anisotropic transport phenomena.…”
mentioning
confidence: 99%
See 2 more Smart Citations